Cognitive behavioural therapy in the treatment of social skills deficits and social phobia in a man with an autism spectrum disorder: a single-case study. (3rd February 2016) - Turner, Mark A.; Hammond, Neil
Abstract: Autism spectrum disorders (ASD) including high-functioning types such as Asperger's syndrome (AS) are diagnosed when there is evidence of a triad of qualitative impairments in social interaction, communication, and stereotyped/repetitive behaviours. It is not uncommon for these impairments to be accompanied by social anxiety. The present single-case study investigates the use of cognitive behavioural therapy (CBT) to treat a 47-year-old man who was assessed as having difficulties with social skills and social phobia in the context of a late diagnosis of AS. He received 20 h of CBT adapted for his AS in 15 sessions including a 1-month follow-up. Following a highly individualized formulation, treatment included modelling, role-playing, reinforcement, thought challenging, and behavioural experimentation. Results from five self-report measures showed continued improvements from the start of therapy to follow-up in social anxiety, global distress, depression and self-esteem. The client gave positive feedback about his experience of treatment. The case study is discussed with reference to limitations and some reflections for CBT in ASD.